Progresses in Chemical Sensor - Wang, Wen (IntechOpen, 2016)
Although the history of chemical sensor dates back not long ago, it has attracted great research interest owing to its many excellent properties such as small size, satisfactory sensitivity, larger dynamic range, low cost, and easy-to-realize automatic measurement and on-line or in situ and continuous detection. With decades of vigorous research works, various sophisticated chemical sensors have been widely used in environmental conservation and monitoring, industrial process monitoring, gas composition analysis, medicine, national defense and public security, and on-site emergency disposal. Hence, the chemical sensor becomes one of the most active and effective directions of modern sensor technology. A typical chemical sensor is the analyzer that responds to a particular analyte in a selective and reversible way and transforms input chemical quantity, ranging from the concentration of a specific sample component to total composition analysis, into an analytically electrical signal. This book is an attempt to highlight recent progresses in the chemical sensors. It is composed of seven chapters and divided into four sections categorized by the working principle of the chemical sensor. This collection of up-to-date information and the latest research progress on chemical sensor will provide valuable references and learning materials for all those working in the field of chemical sensors.